Popliteal Fossa Pain in 24 Year-old Female - Choi, Kwan Woong; Yoon, Kyung Bong; Yoon, Duck Mi; Kim, Do Hyeong (The Korean journal of pain, 2012)
The pain around the posterior knee, called 'popliteal fossa', has been known to be caused by a variety of disease entities. Venous malformation is a very rare cause of popliteal area pain, and its diagnosis is frequently delayed, missed, or given incorrectly. Here, we report a case of a patient with popliteal fossa pain for 2 years and was diagnosed as intramuscular venous malformation using ultrasound.